Study on isothermal fatigue life prediction model of a new type hot stamping die steel 4Cr2Mo2V. (June 2022) - Bin, Jiang; Xiaocheng, Li; Pengpeng, Zuo; Xiaochun, Wu
Graphical abstract: Highlights: The steel 4Cr2Mo2V studied in this paper is a new steel developed by our research group, it has been widely used in hot stamping plants. Now the service life of materials is studied through isothermal fatigue, and the best life model is obtained for better die design. Abstract: In this paper, the isothermal fatigue behavior and life of 4Cr2Mo2V steel for new hot stamping die were studied. Axial tension compression symmetric fatigue tests with different strains were carried out at 300 ℃. When the half strain amplitude was from 0.3% to 0.9%, the response stress continued to soften, and the decline rate of response stress gradually increased, but when the half strain amplitude was 0.9%, the material would fail early. Used Coffin-Manson (C-M), Basquin-Coffin-Manson (BCM) and original Ostergren models to predict the life, the prediction effect was not good. Box-Cox variable transformation was carried out on the cycle life, and then the modified Ostergren model could accurately predict the life. The life prediction model was also established by fitting the response stress curve, but the appropriate d value needs to be set to accurately simulate the life.